Supplemental Efficacy in Tuberculosis Patients: A Systematic Review - Noernahar Septisari Usman; Solikhah Solikhah; Rosyidah Rosyidah; Jin Yi Hwang; Fauzia Farah Az Zahra (Disease Prevention and Public Health Journal, 2023)
Background: Tuberculosis is a disease that continues to be a global issue because it contributes to high death and morbidity rates. To minimize the severity of tuberculosis, nutritional supplements should be given to tuberculosis patients. However, there are only a few studies in the literature that evaluate the impact of supplementation on overall clinical improvement in tuberculosis patients. This study aimed to update the current evidence of supplementation's clinical benefit for tuberculosis patients. Method: The databases Pubmed, Science Drive, and Sage were utilized to search for references to the publications included in this study. Following inclusion and exclusion extraction, seven of the 14,249 items discovered remained. Result: Six of the seven publications found that extra supplementation for tuberculosis patients led to clinical improvement, while one article found no benefit. Vitamin D1000IU, Vitamin D5000IU, Vitamin D2, Channa striata extraction, Calcitrol supplements, Baihe gujin (traditional herbs), and probiotic Lactobacillus casei are just a few of the supplements included in these seven pieces. Conclusion: Supplements can be given to tuberculosis patients in conjunction with anti-tuberculosis therapy because they have been shown to be effective in providing clinical improvement in patients, but their effectiveness is dependent on the type and dose given.